Le personnage comme support d’identification - Vincent Jouve (Cahiers de Narratologie)
The notion of “character”, neglected by the structuralist and semiotic models of the 1960s, has regained a prominent role in the analysis of reading and the study of fiction. After outlining the reasons for this renewed interest, the focus will be on a particular dimension of the reading experience - identification with characters - and on how and why this happens. We'll identify a small number of model supports, distinguishing between what's textual and what's reader-dependent; as an illustration, we'll apply the proposed model to an extract from a novel. Finally, we'll consider the effects of fictional identification and the value of analyzing this notion in a school context.